Boganmeldelser - Bødal, Kåre; Rehof, Lars Adam; Krarup, Ole; Kruse, Sysette Vinding; Kallehauge, H.; Stevnsborg, Henrik; Kyvsgaard, Britta; Christie, Nils; Simonsen, Jørn; Järvinen, Margaretha; m.fl. (Nordisk Tidsskrift for Kriminalvidenskab, 1987)
Book reviews